2009
DOI: 10.1159/000257511
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Patterns in Visceral and Subcutaneous Adipose Depots in Rats are Linked to Their Morphologic Features

Abstract: The aim was to characterize the expression pattern of genes involved in lipid metabolism in internal (retroperitoneal, mesenteric) and subcutaneous (inguinal) adipose tissue depots in rats and their relation with site-specific morphological- and metabolic-features. Gene expression by RT-qPCR, western blot and morphometric analyses were performed. Lipogenesis-related genes (PPARγ2, SREBP1c, ACC1, GPAT, LPL, CD36, GLUT4) showed higher mRNA levels in the retroperitoneal depot versus the mesenteric and the inguina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 42 publications
3
48
0
5
Order By: Relevance
“…ATGL mRNA levels were not determined in the re-fed animals as ATGL expression is not affected by acute re-feeding conditions. 36,37 Effect of age on adiponutrin and ATGL expression The animals used were 6 months old; as age is known to affect expression of molecules involved in energy homeostasis and body weight maintenance, 40,41 we compared the basal expression of adiponutrin and ATGL in 6-month-old control fed animals with 3-month-old ones. The results show a sharp decrease (B76%) with age in adiponutrin expression in the two internal white adipose tissue depots studied, mesenteric and retroperitoneal; ATGL mRNA expression was not affected by age in any depot (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATGL mRNA levels were not determined in the re-fed animals as ATGL expression is not affected by acute re-feeding conditions. 36,37 Effect of age on adiponutrin and ATGL expression The animals used were 6 months old; as age is known to affect expression of molecules involved in energy homeostasis and body weight maintenance, 40,41 we compared the basal expression of adiponutrin and ATGL in 6-month-old control fed animals with 3-month-old ones. The results show a sharp decrease (B76%) with age in adiponutrin expression in the two internal white adipose tissue depots studied, mesenteric and retroperitoneal; ATGL mRNA expression was not affected by age in any depot (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…2,[8][9][10] ATGL levels were only determined in fed and fasted animals because fasting is the most important stimulus affecting the expression of the ATGL gene, 7,18,19 while 3 or 12 h refeeding after fasting does not produce any change in the ATGL mRNA levels attained during fasting. 36,37 Total RNA was extracted using Tripure reagent (Roche, Barcelona, Spain) according to the instructions provided by the supplier. Isolated RNA was quantified using the NanoDrop ND-1000 spectrophotometer (NadroDrop Technologies, Wilmington, DE, USA) and its integrity confirmed using agarose gel electrophoresis.…”
Section: Real-time Quantitative Rt-polymerase Chain Reaction (Q-pcr) mentioning
confidence: 99%
“…33,34 In this sense, in the inguinal depot, the only one that maintains the levels of OB-Rb unaltered after HF-diet feeding, we found increased expression levels of several markers of fatty acid oxidation (PPARa, PGC1, CPT1 and UCP3) in both groups of rats under HF-diet feeding. This increase in fatty acid oxidation capacity occurring in the subcutaneous tissue may be of great importance considering that this tissue has a greater oxidative capacity than internal depots, such as the retroperitoneal fat, 35 and thus its contribution may be quantitatively relevant. It is noteworthy the significant increase (285%) in UCP3 mRNA levels occurring in this depot in leptin-treated rats under HF-diet feeding.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular and genetic basis for these differences remains poorly understood. Many studies on human and rodent adipose tissues have revealed differences in gene expression between anatomically distinct fat depots (Linder et al, 2004;Montague et al, 1998;Palou et al, 2009;Perrini et al, 2008;Tchkonia et al, 2007;van Beek et al, 2007;Vohl et al, 2004;Wu et al, 2008). However, determining whether these differences in gene expression are the cause or consequence of the functional differences has been a challenge.…”
Section: Expression Of Developmental Genes Differs Between Adipose Timentioning
confidence: 99%